2019
DOI: 10.1111/fire.12191
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Increasing Risk Aversion and the Equity Premium Puzzle

Abstract: We introduce a new preference structure—age‐dependent increasing risk aversion (IRA)—in a three‐period overlapping generations model with borrowing constraints, and examine the behavior of equity premium in this framework. We find that IRA preferences generate results that are more consistent with U.S. data for the equity premium, level of savings and portfolio shares, without assuming unreasonable levels of risk aversion. We find that the relative difference between the two risk aversions (how much more risk‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…In fact, a few studies have examined the issue of risk aversion on the macroeconomy, although not with a general equilibrium OLG model. Preferences with increasing risk aversion produce equity premium, savings and portfolio share behaviour that are more consistent with the U.S. data, suggested DaSilva et al (2019) using three-period OLG model without the production sector. Tallarini Jr (2000) considered a business cycle model without overlapping generations and showed that increasing risk aversion, although it does not significantly affect aggregate quantity variables, can improve the asset market predictions and increase the welfare cost of the business cycle.…”
Section: Introductionmentioning
confidence: 52%
“…In fact, a few studies have examined the issue of risk aversion on the macroeconomy, although not with a general equilibrium OLG model. Preferences with increasing risk aversion produce equity premium, savings and portfolio share behaviour that are more consistent with the U.S. data, suggested DaSilva et al (2019) using three-period OLG model without the production sector. Tallarini Jr (2000) considered a business cycle model without overlapping generations and showed that increasing risk aversion, although it does not significantly affect aggregate quantity variables, can improve the asset market predictions and increase the welfare cost of the business cycle.…”
Section: Introductionmentioning
confidence: 52%
“…As their income sources and patterns, as well as risk aversion, change over the life cycle, maintaining similar living standards might thus require shifting the volume and structure of their portfolios. Decreasing risk aversion (usually proxied by the share of risky assets) has been associated with significantly increasing wealth [e.g., Cohn et al, 1975;Riley and Chow, 1992;Wang and Hanna,1997] and with age [Riley and Chow, 1992;DaSilva et al, 2019]. With respect to age, the optimal asset portfolios [see Horneff et al, 2009] should include a large proportion of shares for young investors, which exhibit a downward trend as age increases.…”
Section: Life-cycle Investing and Generationsmentioning
confidence: 99%
“…After Mehra & Prescott (1985) paper on the ERP puzzle, many researchers presented their opinions on how to solve the ERP puzzle, including myopic loss aversion (Thaler & Benartzi, 1995), habit formation of investors (Campbell & Cochrane, 1999;Campbell, 1999) market segmentation theory (Mankiw & Zeldes, 1991), survival bias (Brown & Goetzmann, 1995), and disappointment aversion (Ang, Bekaert & Liu, 2005). Although there is substantial literature on the equity premium puzzle, only a few papers have examined it in emerging economies, but not in Pakistan (Shirvani, Stoyanov, Fabozzi & Rachev, 2020;Kim, 2021;DaSilva, Farka & Giannikos, 2019). Individual investors in emerging markets do not have the same expertise as developed economies (Claus & Thomas, 2001;Bonizzi, 2017).…”
Section: Introductionmentioning
confidence: 99%